Convergencia real en la Unión Europea ampliada - Alonso Guinea, Fernando; Cendejas Bueno, José Luis (Papeles de Europa, 2010)
This paper analyzes the process of real convergence of the economies of the enlarged European Union along the period 1995 to 2009. From per capita GDP figures, it is shown that important progresses in beta convergence have taken place, although they have not been homogeneous between countries nor along the sample period. Some fraction of convergence has been caused by both the statistical effect derived from the weaken growth of the greatest economies, and the migratory flows from the east to the west of the EU. In the last years (2008-09) convergence has stopped, or even reverted, although this dynamic can be appreciated before the beginning of the recession. Continuing converging currently depends on the same factors that delay economic recovery.